2016
DOI: 10.1111/jpn.12591
|View full text |Cite
|
Sign up to set email alerts
|

Liver mitochondrial oxygen consumption and proton leak kinetics in broilers supplemented with dietary copper or zinc following coccidiosis challenge

Abstract: Mitochondrial respiration was assessed in sixteen 7-day-old broilers as a subset of a larger study assessing the effects of Cu and Zn supplementation above requirements with a coccidiosis challenge on gain/feed ratio. The birds were selected from four treatments (four birds/treatment): a control diet (Cu 15 mg/kg and Zn 60 mg/kg) + coccidiosis challenge (CC), a Cu diet with 245 mg/kg Cu from tribasic copper chloride (TBCC) + CC, a negative control diet (Cu 15 mg/kg and Zn 60 mg/kg) - CC and a Zn diet with 2000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Therefore, the increment in liver Cu concentration observed during coccidiosis may be an important mechanism of defense associated with lower levels of cellular induced apoptosis. This was already hypothesized by Acetoze et al (53) when studying the impact of supplementation of Cu and Zn above the requirements of broilers under coccidiosis challenge.…”
Section: Coppermentioning
confidence: 61%
See 1 more Smart Citation
“…Therefore, the increment in liver Cu concentration observed during coccidiosis may be an important mechanism of defense associated with lower levels of cellular induced apoptosis. This was already hypothesized by Acetoze et al (53) when studying the impact of supplementation of Cu and Zn above the requirements of broilers under coccidiosis challenge.…”
Section: Coppermentioning
confidence: 61%
“…Curiously, blood and liver Cu concentration are positively associated with the plasma ceruloplasmin concentration (53), a multicopper enzyme of the family of acute phase proteins that protects cells against the injuries induced by oxidative stress (53). Therefore, the increment in liver Cu concentration observed during coccidiosis may be an important mechanism of defense associated with lower levels of cellular induced apoptosis.…”
Section: Coppermentioning
confidence: 99%
“…The addition of humic substances to the feed for quails (360; 480; 600 mg.kg -1 ) caused an increase in serum Zn (31.47; 35.79; 35.66 µmol.l -1 ) and a decrease in serum Cu (31.47; 35.79; 35.66 µmol.l -1 ) in three supplemented groups compared to the control broilers [4]. Blood and liver Cu concentrations are positively associated with the plasma ceruloplasmin concentration [2]. M i l l e r et al [14] observed the levels of trace elements in sea ducks' blood and found that Cu concentrations differed little among species, site, or age class (adult females versus ducklings), perhaps due to Cu being closely regulated in the blood.…”
Section: Resultsmentioning
confidence: 99%
“…The sample size of cows per treatment (high vs. low) was estimated to be 11, based on a 2-tailed test, with a difference of 30% between electron transport chain enzyme complex activities, with a power of 0.90 and an α of 0.05. Estimates of sample size were based on the cows available for the project and past studies, involving mitochondrial measurements (Acetoze et al, 2017;Niesen and Rossow, 2019), and the minimum sample size was 10 cows per treatment. To be included in the study, cows needed to be at a similar stage of lactation (70 ± 11 DIM) and were fed the same diet using Calan Broadbent Feeding System (American Calan Inc.).…”
Section: Animal Management and Housingmentioning
confidence: 99%